Metabolitos secundarios presentes en extractos herbales promisorios para el tratamiento del cáncer cervical: una revisión sistemática de estudios in vitro. (2022)
Uterine cervical cancer (UCC) is the fourth most common cancer and the third leading cause of mortality in women worldwide. Currently, treatments are limited and/or have side effects; however, natural therapies, with less invasive activity and residual effect, have great potential. It is necessary to investigate the main secondary metabolites of herbal extracts with potential in the treatment of UCC. The aim of this study was to perform a systematic review of the secondary metabolites that show regulate the intrinsic and extrinsic apoptotic pathways in UCC cell lines. A standardized methodology based on PRISMA guidelines was used, executing a Boolean search algorithm in different specialized databases. A total of 16 studies met the inclusion criteria of this systematic review with a low-to-medium risk of bias. For the evaluation of the anticancer effect of herbal extracts and secondary metabolites were used as cell models HeLa, SiHa, ME-180 and CaSki. After convergence analysis, several secondary metabolites with antioxidant effect (terpenoids, flavonoids, alkaloids and caffeic acids) were found to exhibit regulatory effects on apoptotic pathways (intrinsic as well as extrinsic) in different HCC cell models. Further translational research is required to evaluate their potential use as a treatment for HCC.